Autophagy-dependent ferroptosis drives tumor-associated macrophage polarization via release and uptake of oncogenic KRAS protein - Dai, Enyong (Autophagy, 2020)
KRAS is the most frequently mutated oncogene in human neoplasia. Despite a large investment to understand the effects of KRAS mutation in cancer cells, the direct effects of the oncogenetic KRAS activation on immune cells remain elusive. Here, we report that extracellular KRAS(G12D) is essential for pancreatic tumor-associated macrophage polarization. Oxidative stress induces KRAS(G12D) protein release from cancer cells succumbing to autophagy-dependent ferroptosis. Extracellular KRAS(G12D) packaged into exosomes then is taken up by macrophages through an AGER-dependent mechanism. KRAS(G12D) causes macrophages to switch to an M2-like pro-tumor phenotype via STAT3-dependent fatty acid oxidation. Consequently, the disruption of KRAS(G12D) release and uptake can abolish the macrophage-mediated stimulation of pancreatic adenocarcinomas in mouse models. Importantly, the level of KRAS(G12D) expression in macrophages correlates with poor survival in pancreatic cancer patients. These findings not only identify extracellular KRAS(G12D) as a key mediator of cancer cell-macrophage communication, but also provide a novel KRAS-targeted anticancer strategy. Abbreviations: DAMP, damage-associated molecular pattern; PBMCMs, peripheral blood mononuclear cell-derived macrophages; PDAC, pancreatic ductal adenocarcinoma; s.c., subcutaneously; TAMs, tumor-associated macrophages; TME, tumor microenvironment.